1998
DOI: 10.1557/proc-553-13
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication Of High Quality Qc Films Via The Route Of The Amorphous Phase

Abstract: We discuss the preparation of thin icosahedral films (Al-Cu-Fe and Al-Pd-Re) via the route of the amorphous (a-)phase which in some aspects is a precursor to the icosahedral phase. A direct transition from the a-to the i-phase occurs for Al-Cu-Fe films at 430°C on the time scale of minutes. The resulting films are of good quality as shown by diffraction and electronic transport properties. The surface of the resulting films is very smooth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Many investigations performed previously have focused on the presence of an amorphous phase as the precursor to the quasicrystalline one 6,7,8 . However, diffraction patterns of "as-deposited" films in this present work suggest that they were composed of nano-scale grains, which had quasicrystalline and its approximants phase structures.…”
Section: Resultsmentioning
confidence: 99%
“…Many investigations performed previously have focused on the presence of an amorphous phase as the precursor to the quasicrystalline one 6,7,8 . However, diffraction patterns of "as-deposited" films in this present work suggest that they were composed of nano-scale grains, which had quasicrystalline and its approximants phase structures.…”
Section: Resultsmentioning
confidence: 99%
“…Contacts were made to the films using silver paint. Additional details on film preparation and characterization by electron diffraction can be found in [17].…”
Section: Methodsmentioning
confidence: 99%
“…An example of metallic behaviour is shown in figure 1 where the quasicrystal AlPdRe film No C5 exhibits w which tend to zero as T → 0 K. This film has an R(4.2 K)/R(300 K) ratio of 2.4. For this metallic case, a least-squares regression fit of the log(wσ ) versus log T data yields values for the exponent z and the prefactor C, according to equations ( 12) and (17). A value for σ (0) follows directly from one of the data points.…”
Section: Low Temperature Conductivity Data and The Metal-insulator Tr...mentioning
confidence: 99%
“…Thin amorphous 2200 Å films with nominal compositions near Al 72 Pd 20 Re 8 were prepared by co-sputtering with two magnetron sources onto quartz glass substrates, as illustrated in figure 1 [20]. One target source contained an AlPd alloy and the second source contained the Re element.…”
Section: Film Preparation and Measurement Detailsmentioning
confidence: 99%
“…Thus, the possibility of a small shift in composition due to preferential evaporation losses of Al and maybe of Pd cannot be excluded. Details of the film preparation are reported in reference [20]. X-ray diffraction, SEM, and TEM showed that the resulting films are single-phased icosahedral with grain sizes up to 1 µm [20]; the electron micrographs displayed fivefoldsymmetry patterns [21].…”
Section: Film Preparation and Measurement Detailsmentioning
confidence: 99%